2015
DOI: 10.1371/journal.pone.0115782
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effects of an Elastic Knee Sleeve on Frontal Plane Gait Biomechanics in Knee Osteoarthritis

Abstract: IntroductionOsteoarthritis of the knee affects millions of people. Elastic knee sleeves aim at relieving symptoms. While symptomatic improvements have been demonstrated as a consequence of elastic knee sleeves, evidence for biomechanical alterations only exists for the sagittal plane. We therefore asked what effect an elastic knee sleeve would have on frontal plane gait biomechanics.Methods18 subjects (8 women, 10 men) with osteoarthritis of the medial tibiofemoral joint walked over ground with and without an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 33 publications
(52 reference statements)
2
42
0
7
Order By: Relevance
“…We found that wearing a laterally wedged insole significantly increased the valgus moment arm of the subtalar joint, creating a lateral shift in COP location. Although the beneficial effect of reducing knee joint Varus moment with a laterally wedged insole were evident in both the healthy elders and the patients with OA, the patients with OA wearing such an insole had significantly greater knee joint Varus moments during gait compared with healthy elders 23 , this finding could be interpreted as follows: the 6° lateral wedge seems to have a range of effectiveness where it successfully reduces the varus moments in OA patients. Although wearing A 6° lateral wedge reduced the varus moment significantly, it was unable to reduce it to normative levels.…”
Section: Discussionmentioning
confidence: 90%
“…We found that wearing a laterally wedged insole significantly increased the valgus moment arm of the subtalar joint, creating a lateral shift in COP location. Although the beneficial effect of reducing knee joint Varus moment with a laterally wedged insole were evident in both the healthy elders and the patients with OA, the patients with OA wearing such an insole had significantly greater knee joint Varus moments during gait compared with healthy elders 23 , this finding could be interpreted as follows: the 6° lateral wedge seems to have a range of effectiveness where it successfully reduces the varus moments in OA patients. Although wearing A 6° lateral wedge reduced the varus moment significantly, it was unable to reduce it to normative levels.…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, promising results on the influence of compression garments have been shown. Elastic knee sleeves improved knee motions with decreased knee adduction angle and peak knee adduction (Schween et al, 2015), and silicone web braces reduced knee valgus and internal rotation angles (Hanzlikova et al, 2016). Zampporri and Aguinaldo (2017) evaluated the influence of compression tights on knee motion.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that a knee sleeve might alter joint or segment coordination based on the influences of a knee sleeve on the functional capacity and performance associated with the joint or segment kinematics (Bryk et al, 2011; Collins et al, 2014; Mortaza et al, 2012; Schween, Gehring & Gollhofer, 2015). However, to the best of our knowledge, no study has focused on the effects of using knee sleeves on joint or segment coordination.…”
Section: Introductionmentioning
confidence: 99%